Coronavirus Disease 2019 in Pediatric Oncology Patients: A Matched–Cohort Analysis of the SCCM Discovery Viral Infection and Respiratory Illness Universal Study COVID-19 Registry. Issue 3 (12th April 2023) - Balakumar, Niveditha; Catueno, Samanta; Nadiger, Meghana; Keshavamurthy, Prithvi Raj Sendi; Totapally, Balagangadhar R.; Sherani, Farha; Mba, Nkechi; Gist, Katja M.; Tripathi, Sandeep; Gajic, Ognjen; Deo, Neha; Kumar, Vishakha; et al.
Abstract : Background: There is a paucity of multicenter data describing the impact of coronavirus disease 2019 (COVID-19) on hospitalized pediatric oncology patients. Using a large, multicenter, Society of Critical Care Medicine (SCCM) Discovery Viral Infection and Respiratory Illness University Study (VIRUS) database, we aimed at assessing outcomes of COVID-19 infection in this population. Method: This is a matched-cohort study involving children below 18 years of age hospitalized with COVID-19 between March 2020 and January 2021. Using the VIRUS; COVID-19 Registry database, children with oncologic diseases were compared with propensity score matched (age groups, sex, race, and ethnicity) cohort of children without oncologic diseases for the prevalence of Multisystem Inflammatory Syndrome in Children (MIS-C), intensive care unit (ICU) admission, interventions, hospital, and ICU length of stay. Results: The number of children in the case and control groups was 45 and 180, respectively. ICU admission rate was similar in both groups ([47.7 vs 51.7%], P =0.63). The proportion of children requiring noninvasive and invasive mechanical ventilation, and its duration were similar between groups, same as hospital mortality. Interestingly, MIS-C was significantly lower in the oncology group compared with the control (2.4 vs 24.6%; P =0.0002). Conclusions: In this study using a multicenter VIRUS database, ICU admission rate, interventions, and outcomes of COVID-19 were similar in children with the oncologic disease compared with control patients. The incidence of MIS-C is lower in oncologic patients.